Drivers, Measures and Outcomes of Luxury Flagship Store Experience - Islam, Mohammad Majedul (Curtin University, 2022)
The luxury flagship store experience (LFSE) and luxury flagship store attributes (LFSA) involve multi-faceted aspects that have received reasonably less attention in the extant literature. This thesis attempts to dive deep into the topic of the ‘luxury flagship store experience’, extending the concept in terms of dimensions, drivers and outcomes. The research comprises mixed-methods studies to attain the research objectives. The findings revealed three dimensions of the LFSE and four for the LFSA constructs. This study also assessed the model constructs’ relationships and tested 22 hypotheses. The research findings offer a better understanding of consumer responses during shopping at, or visiting, a luxury flagship store and contribute to the extant body of knowledge in several ways.